Case Report: Complete Remission of a Patient With Metastatic Gastric Cancer Treated With Nivolumab Combined With Chemotherapy After Palliative Surgery - Dai, Peilin; Rao, Xi; Zhang, Xi; Qiu, Enming; Wu, Gang; Lin, Yu; Li, Sitong; Li, Zhou; Cai, Zhai; Han, Shuai (Frontiers in Immunology, 2022)
Metastatic advanced gastric cancer, for which treatment strategies are extremely limited, has a poor prognosis. Complete remission is rare. Patients usually lose the opportunity of therapeutic surgery because the lesions cannot be completely removed, although it can greatly prolong their survival time. Palliative surgery usually suggests bad outcomes. In recent years, the immune checkpoint inhibitor (ICI) nivolumab has shown significant efficacy in the treatment of advanced gastric cancer. However, its applicable conditions and optimal withdrawal time remain controversial owing to its low response rate and high incidence of immune-related adverse events. Herein, we introduce a 66-year-old male patient with advanced gastric cancer with multiple liver metastases who underwent laparoscopic total gastrectomy for acute gastric bleeding. The patient received eight cycles of S-1 plus oxaliplatin (SOX) and switched to eight cycles of SOX plus nivolumab combined regimen in a stable state, later achieving complete remission. There was no recurrence for 32 months after the surgery. This is the first reported case of gastric cancer with multiple liver metastases with long-term complete remission with nivolumab treatment after palliative surgery. The potential mechanism of complete remission was discussed through clinical, genomic, and immune characteristics. The patient had a history of psoriasis and was positive for programmed death ligand 1 (PD-L1), and the interaction of TP53 mutation and HER-2 (-) gene may be associated with complete remission.